Status and Recommendations for Incorporating Biomarkers for Cutaneous Neurofibromas Into Clinical Research. Issue 7 (17th August 2021) - Wallis, Deeann; Stemmer-Rachamimov, Anat; Adsit, Sarah; Korf, Bruce; Pichard, Dominique; Blakeley, Jaishri; Sarin, Kavita Y.
Abstract : Objective: To summarize existing biomarker data for cutaneous neurofibroma (cNF) and to inform the incorporation of biomarkers into clinical trial design for cNFs. Methods: The cNF working group, a subgroup of the Response Evaluation in Neurofibromatosis and Schwannomatosis (REiNS) consortium, was formed to review and inform clinical trial design for cNFs. Between June 2018 and February 2020, the cNF working group performed a review of existing data on genetic biomarkers for cNFs in the setting of neurofibromatosis type 1. We also reviewed criteria for successful biomarker application in the clinic. The group then held a series of meetings to develop a consensus report. Results: Our systematic literature review of existing data revealed a lack of validated biomarkers for cNFs. In our report, we summarize the existing signaling, genomic, transcriptomic, histopathologic, and proteomic data relevant to cNF. Finally, we make recommendations for incorporating exploratory aims for predictive biomarkers into clinical trials through biobanking samples. Conclusion: These recommendations are intended to provide both researchers and clinicians with best practices for clinical trial design to aid in the identification of clinically validated biomarkers for cNF.